Mixed Pulmonary Adenocarcinoma and Atypical Carcinoid: A Report of Two Cases of a Non-codified Entity With Biological Profile - Parente, Paola; Rossi, Antonio; Sparaneo, Angelo; Fabrizio, Federico Pio; Centonza, Antonella; Taurchini, Marco; Mazza, Tommaso; Cassano, Maurizio; Miscio, Giuseppe; Centra, Flavia; Ferretti, Gian Maria; Di Micco, Concetta Martina; et al. (Frontiers in Molecular Biosciences, 2021)
Pulmonary carcinoids combined with a non-neuroendocrine component have rarely been described, and these histological subtypes are not included as a specific entity in the current World Health Organization classification of pulmonary neoplasms. Here we described the molecular and histological features of two rare cases of mixed lung neoplasms, composed of atypical carcinoid and adenocarcinoma. The targeted next-generation sequencing analysis covering single nucleotide variations, copy number variations, and transcript fusions in a total of 161 cancer genes of the two different tumor components shows a similar molecular profile of shared and private gene mutations. These findings suggest their monoclonal origin from a transformed stem/progenitor tumor cell which acquires a divergent differentiation during its development and progression and accumulates novel, specific mutations.